2006
DOI: 10.1158/1078-0432.ccr-06-0369
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of FOXP3+ Regulatory T Cells Increases During the Progression of Pancreatic Ductal Adenocarcinoma and Its Premalignant Lesions

Abstract: Purpose: Antitumor immune response changes drastically during the progression of cancers.Established cancers often escape from the host immune system, although specific immune surveillance operates in the early stages of tumorigenesis in murine models. CD4 + CD25+ regulatory T cells (T R ) play a central role in self-tolerance and suppress effective antitumor immune responses. The aim of this study was to investigate the clinical significance and roles of T R in the progression and multistep carcinogenesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

47
540
4
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 707 publications
(596 citation statements)
references
References 41 publications
47
540
4
5
Order By: Relevance
“…Moreover, the population of Foxp3 þ cells in stage IV was significantly larger than those in stage I. However, the prevalence of Foxp3 þ cells is not significantly associated with the overall survival of patients with gastric cancer, in contrast with previous reports on ovarian carcinoma (Wolf et al, 2005) and pancreatic cancer (Hiraoka et al, 2006). The present study is, to our knowledge, the first report describing the prevalence of Foxp3 þ T regs related to the prognosis in gastric cancer.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Moreover, the population of Foxp3 þ cells in stage IV was significantly larger than those in stage I. However, the prevalence of Foxp3 þ cells is not significantly associated with the overall survival of patients with gastric cancer, in contrast with previous reports on ovarian carcinoma (Wolf et al, 2005) and pancreatic cancer (Hiraoka et al, 2006). The present study is, to our knowledge, the first report describing the prevalence of Foxp3 þ T regs related to the prognosis in gastric cancer.…”
Section: Discussioncontrasting
confidence: 77%
“…Furthermore, the high prevalence of CD4 þ CD25 þ T regs is closely associated with a poor prognosis in ovarian (Curiel et al, 2004) or pancreatic (Liyanage et al, 2002) cancer. Recently, intratumoral Foxp3 þ T regs in ovarian (Wolf et al, 2005) or pancreatic (Hiraoka et al, 2006) cancer were correlated with a poor prognosis (Wolf et al, 2005;Hiraoka et al, 2006). In particular, multivariate analysis in pancreatic cancer (Hiraoka et al, 2006) showed that the prevalence of Foxp3 þ T regs was an independent prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For several solid tumors, there is a clear correlation between high T reg numbers (tumor infiltrating or circulating in the peripheral blood) and a poor prognosis. 10,11,21,22 Although previous reports have indicated an increase of T regs in the peripheral blood of patients with CLL compared with healthy controls, 19,20 their role in disease progression has remained unclear. The objective of the present study was to elucidate the possible clinical relevance of T reg numbers in early stage CLL.…”
Section: Discussionmentioning
confidence: 99%
“…of T regs (tumor infiltrating or circulating in the peripheral blood) and a poor prognosis, [10][11][12] we investigated the role of T regs in early stage CLL.…”
mentioning
confidence: 99%